化脓性汗腺炎研究的核心结果的全球共识:历史性共识会议I和II的更新. (29th March 2018) - Thorlacius, L.; Garg, A.; Ingram, J.R.; Villumsen, B.; Theut Rii, P.; Gottlieb, A.B.; Merola, J.F.; Dellavalle, R.; Ardon, C.; Baba, R.; Bechara, F.G.; Cohen, A.D.; et al.
Abstract : Linked Article:  Thorlacius et al. Br J Dermatol 2018;178 :715–721